A Practical Approach to Quasi-convex Optimization: Sompong Dhompongsa, Poom Kumam, Konrawut Khammahawong - Team, Support (Thai Journal of Mathematics, 2022)
A new and simple method for quasi-convex optimization is introduced from which its various applications can be derived. Especially, a global optimum under constrains can be approximated for all continuous functions.